The Influence of Emotion on Cognitive Control: Relevance for Development and Adolescent Psychopathology - Mueller, Sven (Frontiers in Psychology, 2011)
The last decade has witnessed an explosion of research into the neural mechanisms underlying emotion processing on the one hand and cognitive control and executive function on the other hand. More recently, studies have begun to directly address interactions between emotion and cognitive control but many questions remain currently unresolved. Interestingly, parallel to investigations in healthy adults, research in developmental cognitive neuroscience and developmental affective disorders has provided some intriguing findings that complement the adult literature. The goal of this review is to provide an overview of current research on cognitive control and emotion interactions and integrate parallel lines of research in adulthood and development. To this aim, the review will draw on several lines of evidence ranging from behavioural, neurophysiological, and neuroimaging work in healthy populations to work in adult and pediatric patients with affective disorders. However, a particular emphasis is given to studies that provide information on the neurobiological underpinnings of emotional and cognitive control processes. Open areas of research for future study will be identified and discussed with regards to current theories on cognitive control and emotion processing.